Odpowiedzi

2010-04-06T13:27:54+02:00
5m+2k=15m-3z
5m - 15m = -3z-2k
-10m=-3z-2k /:(-10)
m=0,3z + 0,2k

E=mgh+ (mv²/2) /*2
2E=2mgh+ mv²
2E = m (2gh+v^2) /:(2gh+v^2)
(2E)/(2gh+v^2)= m
m=(2E)/(2gh+v^2)
2 2 2
2010-04-06T13:28:51+02:00
A) 5m+2k=15m-3z
5m - 15m = -3z - 2k
-10m = -3z - 2k /: (-10)
m = (-3z - 2k) : (-10)
m = 0,3z + 0,2k

b) E=mgh+ (mv²/2)
E = mgh+ (mv²/2) / x 2
2E = 2mgh+ mv²
2E = m (2gh+v²) / : (2gh+v²)
m=(2E) / (2gh+v²)
1 1 1
2010-04-06T13:43:03+02:00
5m-15m=-3z-2k
m(5-15)=-(3z+2k)
m*(-10) =-(3z+2k)
m=(3z+2k)/10
m=3z/10+2k/10
m=0,3 *z + 0,2*k

E=m(gh+v²/2)
m=E/(gh+v²/2)
m=E/(2gh/2+v²/2)
m=E/(2gh+v²)/2
m=2E/(2gh+v²)